Assessing the vulnerability of sensitive species in Mediterranean fisheries: insights from productivity-susceptibility analysis - Li Veli, Daniel; Barrionuevo, Jose Carlos Baez; Bargione, Giada; Barone, Giulio; Bdioui, Marouene; Carbonara, Pierluigi; Fahim, Reda Magdy; Follesa, Maria Cristina; Gökçe, Gökhan; Mahmoud, Hatem Hanafy; Ligas, Alessandro; Idrissi, Mohammed Malouli; et al. (Frontiers in Marine Science, 2024)
Mortality resulting from interactions with fishing gears represent an important threat to sensitive species globally. In this study, we address this issue by defining five species groups of marine megafauna (marine mammals, seabirds, demersal and pelagic elasmobranchs, and sea turtles), and conducting a productivity-susceptibility analysis (PSA) within the context of data-limited fisheries in the Mediterranean and Black Sea. Although there are significant differences among species within each group, this approach has been considered much more direct and functional for management purposes. The productivity (P) of each species group was determined by evaluating a set of attributes averaged across representative species within each group. Species groups’ susceptibility (S) to bycatch was assessed through a comprehensive review of existing literature and expert judgment, considering a series of semi-quantitative attributes. Our analysis identified areas and fishing gears posing potential risks to the species groups assessed, highlighting that sea turtles and elasmobranchs face the potential risk of incidental captures from various fishing gears operating in both neritic (bottom trawls, set nets and bottom longlines) and pelagic (drifting longlines) environments. Marine mammals exhibit moderate risk across most fishing gears, with particular concern for the harbour porpoise Phocoena phocoena relicta in the Black Sea, primarily due to the interaction with set nets, which can severely impact entire population even capturing few specimens due the species low productivity. Seabirds face reduced impact with fishing activities, irrespective of the type of gear examined or the specific area under investigation. Overall, our study highlights the specific basins and fishing gears requiring focused management measures, mitigation strategies, and enhanced monitoring activities to mitigate the impacts of bycatch on vulnerable marine megafauna.